ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR TINGKAT PROFITABILITASS PADA PT MEKAR JAYA TANI GEBANG CIREBON - Widodo Widodo (Jurnal Strategik, 2017)
ABSTRACT The purpose of this study is to study how the level of economic benefits at PT. Mekar Jaya Tani Gebang, Cirebon, based on the 2013-2017 financial report. Data collected in this study were taken from two sources, namely primary sources (interviews and questionnaires) and secondary sources (library research and documentation). Processing is done through ratio calculation. The results showed that the Economic Profitability ratio of PT. Mekar Jaya Tani Gebang Cirebon continued to increase from 2013 to 2017 compared to the average, this proves that things are not good for the company because this means the company is increasingly difficult in managing its capital to generate profits.